Religion in secular society - Singh, N. K. (New Delhi, 2005)
This book is an analytical study of the nature and transformation of religions in secular society. Here we have tried to focus on the conflict and consensus between religion and secular society. As the institutions of secular society grew apart, the religious institutions and their functionaries lost their control over various social activities and the civil authority gained in power. The emergence of new classes with new skills and resources, who were not accommodated in the religious institutions, made the first properly instituted invasion on the spiritual monopoly.
Keywords: Secular society